ACADEMICIAN B. ORUZBAEVA AND ISSUES OF THE STATE LANGUAGE: SCIENTIFIC VIEWS AND CITIZENSHIP POSITION (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article talks about the scientific and civil views of a prominent representative of Kyrgyz linguistics, Academician B. Oruzbaev, on the issue of the state language. Attention is drawn to their relevance and practical value.
Keywords: reconstruction, strength assessment, reliability of operation, strengthening of foundations, brick walls, reinforced concrete slabs, columns, beams and metal structures, restoration of reliability.